THE USAGE OF JADID METHODS IN DEVELOPING YOUTH LEARNING COMPETENCE - Kurbanova, Sevara (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article discusses the usage of Jadid methods in developing youth learning competence. The Jadid method is a teaching approach that emphasizes active and practical learning, individualized learning, and cultural relevance. This article highlights the key features of this approach and how it can be applied in practice to promote effective learning outcomes for young learners.